Kolaborasi Komunitas dalam Pojok Literasi Arjuna untuk Meningkatkan Literasi Digital Anak Desa Sukaharja - Nadila Utami, Hera; Lathifah, Suci; Adinda, Syarlla; Rizkia Maulidya, Finna; Hadi Nugraha, Akmal; Putri Utomo, Endrastiasti; Alfitriani, Shanda (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
The digital era requires children to acquire digital literacy skills from an early age, yet the digital divide remains a major challenge in rural areas. This article describes the implementation of the Pojok Literasi Arjuna (Arjuna Literacy Corner) in Sukaharja Village, Cijeruk District, Bogor Regency, as a community-based collaborative effort to improve children’s digital literacy. The method applied was a community participatory approach consisting of needs assessment, program design, implementation, and evaluation stages. The subjects were 30 children at the elementary to junior high school level, supported by teachers, village cadres, parents, youth organizations, and the village government. The results show a significant improvement in children’s digital literacy. Quantitatively, the average score increased from 56.7 to 78.5, representing a 38.4% improvement. The most notable progress was in identifying credible information sources (45%) and the use of learning applications (42%), while productive skills such as creating digital presentations improved by 30%. Qualitative findings revealed that children became more confident in using digital devices for learning, and parents reported a positive behavioral shift as children increasingly used the internet for educational purposes. Teachers and village cadres served as facilitators adapting the materials to local contexts, while youth organizations acted as role models in the healthy use of digital media. These findings confirm that community collaboration can establish a sustainable digital literacy ecosystem in rural areas. The program not only enhanced children’s digital skills but also strengthened community participation and holds potential for replication in other villages as a community-based empowerment model supporting the achievement of the SDGs.